Preparation and Characterization of Hydrophobic Alginate Derivative Nanocapsules Entrapping l-Cyhalothrin - Hu, Wentao; Li, Jiacheng; Hou, Hongwei; Yan, Huiqiong; Feng, Yuhong; Mi, Xue; Lin, Qiang (Asian Journal of Chemistry, 2013)
Hydrophobic alginate derivative was synthesized by the amidation of alginate and octylamine. The generated octyl-grafted alginate-amide was confirmed by FTIR and 1H NMR. The degree of substitution was 0.23 and whose critical aggregation concentration in aqueous medium was 0.34 mg/mL. This strategy of nanocapsule formulation was based on microemulsion template with octyl-grafted alginate-amide derivative. The morphology and the size of nanocapsules were characterized by transmission electron microscopy, whose average size is 25.78 nm. The nanocapsule has a high loading efficiency valve of 99.95 %. The release characteristics of the nanocapsules were evaluated in methanol and the results indicated that the nanocapsules restrained the release of l-cyhalothrin.